Estudo comparativo da resistência à corrosão entre aços alto manganês e o aço 9% níquel em soluções aquosas de H2SO4 e NaCl - Cerra Florez, Mauro Andres (2017)
Liquefied natural gas volumes which at present have to be stored and/or transported require that the materials engineering constantly develop materials that adapt to the mechanical, chemical and economic needs of the industry. Aluminum alloys, 9% nickel steel alloys and austenitic stainless steels are currently used for cryogenic applications, however, all these materials have disadvantages, such as high cost of production, welding difficulties, corrosion resistance, among others. High manganese steels offer an attractive alternative because manganese and carbon replace nickel as austenite stabilizer; this change also represents a significant decrease in steel fabrication costs. The present study aims to establish a comparative degree of corrosion resistance in two aqueous solutions between four high manganese steels with a content of 28% Mn, 26% Mn, 22% Mn, 20% Mn in relation to the 9% Nickel that is widely used in petrochemical industry. Mass fraction diagrams were performed in Thermo-Calc® software. The steels were characterized using the techniques: Optical Microscopy, Scanning Electron Microscopy (SEM), Electron Backscatter Diffraction Analysis (EBSD), Energy Dispersive X-ray Spectroscopy (EDS), Optical Emission Spectroscopy, X-ray Fluorescence. The mechanical properties were evaluated by hardness and microhardness measurements. The corrosion resistance was evaluated in aqueous solutions of NaCl and H 2 SO 4 by Open Circuit Potential (OCP), Linear Polarization Curves and Electrochemical Impedance Spectroscopy. The results obtained in the thermodynamic study helped to predict the phases present in these steels as well as the heat treatment temperature. The microstructural study revealed the influence of the phases on the mechanical properties, showing that the 9% nickel steel presents higher hardness values than the high manganese steels. The corrosion tests showed that the high manganese steels have less corrosion resistance than 9% nickel steel, due to the formation of unstable and poorly compacted oxides that do not provide protection against corrosion; In contrast, the oxides formed by the 9% nickel steel gave it a better protection as observed in the curves that were found.